2022
DOI: 10.1038/s41392-022-01178-6
|View full text |Cite
|
Sign up to set email alerts
|

The evolving view of thermogenic fat and its implications in cancer and metabolic diseases

Abstract: The incidence of metabolism-related diseases like obesity and type 2 diabetes mellitus has reached pandemic levels worldwide and increased gradually. Most of them are listed on the table of high-risk factors for malignancy, and metabolic disorders systematically or locally contribute to cancer progression and poor prognosis of patients. Importantly, adipose tissue is fundamental to the occurrence and development of these metabolic disorders. White adipose tissue stores excessive energy, while thermogenic fat i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 395 publications
1
9
0
Order By: Relevance
“…The other was the mMCP-counter algorithm, which analyzed the abundance of 16 types of murine immune and stromal cells. Consistent with the thermogenic activation of brown fat in acute cold ( 25 , 26 ), most datasets showed changes started as early as a cold duration of 6h in BAT. These algorithm analyses revealed that beige adipogenesis might occur during longer periods of cold exposure, as 35d long-term cold acclimation resulted in more significant changes in immune cells in SAT ( Table 1 ).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The other was the mMCP-counter algorithm, which analyzed the abundance of 16 types of murine immune and stromal cells. Consistent with the thermogenic activation of brown fat in acute cold ( 25 , 26 ), most datasets showed changes started as early as a cold duration of 6h in BAT. These algorithm analyses revealed that beige adipogenesis might occur during longer periods of cold exposure, as 35d long-term cold acclimation resulted in more significant changes in immune cells in SAT ( Table 1 ).…”
Section: Resultssupporting
confidence: 69%
“…Some significant changes in immune cells, including naĂŻve T (both CD4 + and CD8 + ) cells and memory T (both CD4 + and CD8 + ) cells were only discovered in BAT, but not in SAT. These differences might reveal inherent unique characteristics of BAT during cold exposure, as brown adipocytes are activated rapidly in response to acute cold challenge, while beige adipocytes in SAT are transdifferentiated from white adipocytes or derived from white pre-adipocytes ( 26 ). Immune cells and adipocytes in adipose tissues may interact during these processes, resulting in different changes in immune cells in BAT from those in SAT.…”
Section: Discussionmentioning
confidence: 99%
“…Beige adipocytes improve energy metabolism by enhancing non-shivering thermogenesis. Promoting the browning of WAT is a research hotspot of obesity intervention ( Yin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] WAT exists in excess energy in the form of triacylglycerol (TAG), while thermogenic adipose tissue dissipates energy as heat. [18][19][20][21][22][23] Although both aforementioned strategies are promising, they also possess respective superiority and drawbacks. PDT works rapidly and directly but is only suitable for superficial treatment as limited by light penetration depth.…”
Section: Introductionmentioning
confidence: 99%